Synthesis and characterization of pH-sensitive thiol-containing chitosan beads for controlled drug delivery applications - Jayakumar, R. (2007)
The aim of this study was to develop chitosan-based materials in drug delivery systems possessing covalent attachment of thiol moieties. Thiol-containing chitosan (TCS), found to be soluble in water, was synthesized by graft copolymerization technique. The TCS beads were prepared by using tripolyphoshate, at pH 4.0. The morphology of TCS beads was examined by scanning electron microscopy. The in vitro drug release behavior was studied in phosphate buffer solution at various pH, using indomethacin as a model drug at two different concentrations (0.3 and 0.6% w/w). The release amounts of indomethacin from TCS beads were higher increasing pHs in the dissolution medium. The release rate of indomethacin at pH 7.4 was higher than the release rate at pH 1.4 due to ionization of thiol groups and high solubility of indomethacin in an alkaline medium. These results indicated that the TCS beads may become a delivery system for the controlled release of different drugs wherever pH sensitive mechanics might be useful. This is especially applicable in cases when it is important to minimize drug release in acidic sites, such as in the stomach.